Fuzzy Logic Based Advance Speed Control of Induction Motor - Hore, Debirupa (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
The speed control of Induction motor is done using the advance AI Technique methods. In this System the vector control scheme in the stator flux oriented reference frame is used for controlling the variable speed Induction motor. For this the conventional Speed PI controller and Current PI Controllers are tuned and the responses are observed. The Conventional Speed PI Controller is then replaced by the Fuzzy Logic Speed Controller to observe the various responses of the system. The fuzzy Logic Speed Controller is designed and tuned in such a way to obtain better and fast sped responses of the system. Simulation results reveal that the fuzzy-controller improves the performance of variable speed Induction Motor in terms of speed and Power factor